Incorporating the Principles of Acceptance and Commitment Therapy into Equine-Assisted Psychotherapy. - 1 Roberta Caiazza, 1Toby King, 2 Melissa Davis, 2 Eva Lee, 2 Gwyneth Doherty-Sneddon (Marp Edizioni, 2022)
Equine-assisted psychotherapy is a promising new psychotherapeutic intervention designed to treat a variety of mild to moderate mental health conditions, however it appears to lack a strong psychological framework underpinning the methodology. The Acceptance and Commitment therapy model compliments equine-assisted psychotherapy, with both approaches encouraging clients be in the 'present moment' and focused on committed action. We highlight how these two therapeutic interventions can be incorporated and aligned together to create an effective evidenced-based treatment for mental health conditions. Discussions on the similarities will address how each model can overlap each other.